A nitrogen-doped high-entropy alloy electrocatalyst with hierarchical pore structure and a preparation method and application thereof
Patent Information
- Application Number
- CN202611262786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-08-18
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]针对现有技术中存在的问题,本发明提供一种具有分级孔结构的氮掺杂高熵合金电催化剂及其制备方法和应用,从而解决现有锌空气电池技术缺乏满足低成本、高活性与高稳定性要求的双功能电催化剂,无法有效解决氧还原(ORR)和氧析出(OER)反应动力学缓慢的技术问题
本发明公开一种具有分级孔结构的氮掺杂高熵合金电催化剂的制备方法,该方法通过原位构筑策略,有效解决了锌空气电池双功能催化剂在成本、活性和稳定性上的难题。其核心在于利用高含量的锌盐作为牺牲模板,在后续的高温热处理步骤中,锌元素会优先气化挥发,从而在材料内部原位形成丰富的分级孔结构,这不仅极大地增加了电化学活性面积,也促进了反应物质的传输,从而加速了缓慢的氧还原(ORR)和氧析出(OER)反应动力学。同时,剩余的钼、钨、钴、铁、镍等多种金属元素在高温下合金化,形成高熵合金纳米颗粒,其独特的电子结构和多主元协同效应有助于优化反应中间体的吸附能,进一步提升本征催化活性。此外,使用含氮有机配体(如1H-1,2,3-三氮唑)确保了碳基体的高氮掺杂,能与金属形成牢固的M-N配位键,将高熵合金纳米颗粒稳定地锚定在多孔碳载体上,显著提高了催化剂的长期稳定性。最终,该方案采用储量丰富的非贵金属,从源头上保证了低成本,并通过一步法同时实现了多孔结构、高熵合金和高氮掺杂的协同构建,从而获得了一种兼具高活性与高稳定性的非贵金属双功能电催化剂。即本发明基于Zn的动态造孔效应,利用高熵合金前驱体中Zn元素与Fe、Co、Ni、Mo、W等主元在沸点上的显著差异,通过高温热解使Zn优先气化逸出,在碳基质中原位形成分级孔结构,同时借助合金表面金属原子对碳层石墨化的催化作用以及多主元间的缓慢扩散效应,实现高熵合金纳米颗粒在碳载体中的稳定锚定与电子结构调控,同时将1H-1,2,3-三氮唑作为配体,在热解的时候实现高氮掺杂,为FeCoNiMoW高熵合金组合解决了低ORR的问题,同时保留了其优异OER性能的特点。
Smart Images

Figure CN122992094A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal and energy storage technology, and relates to a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure, its preparation method and application. Background Technology
[0002] Since the beginning of the 21st century, rapid global industrialization and continuous population growth have led to ever-increasing energy demand, exacerbating energy crises and resource shortages. This massive energy consumption not only results in resource scarcity but also exacerbates the imbalance in energy supply. Simultaneously, the extensive use of fossil fuels is accompanied by the emission of greenhouse gases and harmful gases, intensifying climate change and environmental pollution. Against this backdrop, electrochemical energy systems have emerged as one of the most important potential alternatives to traditional fossil fuels, with battery technology occupying a central position in electrochemical research.
[0003] Currently, although the production technology of traditional commercial batteries (such as lithium-ion batteries, lithium-sulfur batteries, and lead-acid batteries) is mature, problems such as high production costs, low efficiency, electrolyte leakage, and safety hazards have not been effectively solved. Among many new battery technologies, metal-air batteries are emerging as a more promising energy technology due to their low cost, high power density, and good sustainability. Metal-air batteries use inexpensive metals (Zn, Al, Fe, Li, Mg, etc.) as the negative electrode and oxygen from the air as the positive electrode active material, eliminating the need to store positive electrode materials and significantly reducing production costs. While lithium-air batteries theoretically have a specific energy as high as 5928 Wh·kg⁻¹,… - ¹ However, the high reactivity of lithium metal in air or aqueous electrolytes leads to serious instability problems. Magnesium-air and aluminum-air batteries suffer from rapid self-discharge and poor coulombic charge efficiency. In contrast, zinc metal is more stable in aqueous electrolytes, and the theoretical energy density of zinc-air batteries (ZAB) can reach 1200 Wh·kg⁻¹. - ¹This is 3 to 4 times that of lithium-ion batteries, and zinc resources are abundant and inexpensive, possessing excellent characteristics such as high volumetric energy density, recyclability, and high specific capacity. An ideal ZAB cathode catalyst must simultaneously satisfy the following requirements: a high half-wave potential (E) in terms of ORR. 1 / 2 ) and a near-4-electron transfer pathway; the OER side exhibits low overpotential and a low Tafel slope. However, ORR and OER involve different oxygen-containing intermediates ( OOH, O、 The adsorption energy of OH at a single metal site is limited by scaling relationships and difficult to optimize simultaneously—this is one of the core challenges in the field of electrocatalysis. Currently, the development of zinc-air batteries mainly faces problems such as low activity and poor stability of the air cathode catalyst, carbonated electrolyte and leakage, low utilization rate of the zinc anode, and short cycle life. Among these, the O=O bond energy at the battery cathode during charging and discharging (498 kJ mol) is a significant concern. -1 The formation / destruction of metal-air secondary batteries requires significant energy (high overpotential), and the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are complex and kinetic processes that limit their practical application. Therefore, the rational construction of low-cost, highly active, and highly stable bifunctional catalysts has become a current research focus and hot topic.
[0004] Currently, platinum (Pt)-based noble metal catalysts remain the benchmark materials for electrochemical efficiency (OER), while IrO2 / RuO2 is the standard for reactive oxygen species (ORR). However, the inherent drawbacks of noble metals, such as their scarcity, high price, and insufficient long-term stability, severely restrict the large-scale application of zinc-air batteries. Although researchers have explored various single non-noble metal alternatives, such as transition metal oxides, carbon-based nanomaterials, and single-atom catalysts, these materials often present irreconcilable contradictions in terms of electrochemical activity, stability, and durability. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure, its preparation method, and its application. This solves the technical problem that existing zinc-air battery technology lacks bifunctional electrocatalysts that meet the requirements of low cost, high activity, and high stability, and cannot effectively solve the slow kinetics of oxygen reduction (ORR) and oxygen evolution (OER) reactions.
[0006] This invention is achieved through the following technical solution: A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: S1: Dissolve zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt in a mixed solvent, and then add nitrogen-containing organic ligands while stirring to carry out a solvothermal reaction to obtain a metal-organic framework precursor; the mixed solvent is a mixture of ethanol, deionized water, N,N-dimethylformamide, and ammonia. S2: The metal-organic framework precursor is subjected to high-temperature heat treatment under a protective atmosphere, so that some metal elements volatilize to form a hierarchical pore structure in situ, while the remaining metal elements are alloyed to form high-entropy alloy nanoparticles, and finally nitrogen-doped high-entropy alloy electrocatalyst is obtained.
[0007] Optionally, the zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt are at least one of the chloride, acetylacetone salt, and nitrate salts of the corresponding metals.
[0008] Optionally, the nitrogen-containing organic ligand is 1H-1,2,3-triazole.
[0009] Optionally, the ratio of ethanol, deionized water, N,N-dimethylformamide and ammonia is 2:3:2:1.
[0010] Optionally, the temperature of the solvothermal reaction is 120~160℃ and the time is 12~36 h.
[0011] Optionally, the nitrogen-containing organic ligand is added at a rate of 2.5 mL / (5-10) min.
[0012] Optionally, the molar ratio of the zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt is 20:1:1:1:1:1.
[0013] Optionally, the high-temperature heat treatment is performed at a temperature of 800~1000℃ and for a holding time of 1~3 hours.
[0014] A nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure was prepared by the method described above.
[0015] The above-mentioned application of a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure in zinc-air batteries.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure. This method effectively solves the challenges of cost, activity, and stability in bifunctional catalysts for zinc-air batteries through an in-situ construction strategy. The core of this method lies in using a high-content zinc salt as a sacrificial template. During the subsequent high-temperature heat treatment step, zinc preferentially vaporizes and volatilizes, thereby forming a rich hierarchical porous structure in situ within the material. This not only significantly increases the electrochemical active area but also promotes the transport of reactants, thus accelerating the slow oxygen reduction (ORR) and oxygen evolution (OER) reaction kinetics. Simultaneously, the remaining molybdenum, tungsten, cobalt, iron, nickel, and other metal elements are alloyed at high temperatures to form high-entropy alloy nanoparticles. Their unique electronic structure and multi-principal synergistic effect help optimize the adsorption energy of reaction intermediates, further enhancing intrinsic catalytic activity. Furthermore, the use of nitrogen-containing organic ligands (such as 1H-1,2,3-triazole) ensures high nitrogen doping of the carbon matrix, enabling the formation of strong MN coordination bonds with the metal. This stably anchors the high-entropy alloy nanoparticles onto the porous carbon support, significantly improving the long-term stability of the catalyst. Finally, this approach utilizes abundant non-precious metals, ensuring low cost from the outset. A one-step method simultaneously achieves the synergistic construction of porous structures, high-entropy alloys, and high nitrogen doping, resulting in a non-precious metal bifunctional electrocatalyst that combines high activity and high stability. This invention is based on the dynamic pore-forming effect of Zn. It utilizes the significant difference in boiling point between Zn and the main components such as Fe, Co, Ni, Mo, and W in the high-entropy alloy precursor. Through high-temperature pyrolysis, Zn preferentially vaporizes and escapes, forming a hierarchical pore structure in situ in the carbon matrix. At the same time, by leveraging the catalytic effect of metal atoms on the graphitization of the carbon layer on the alloy surface and the slow diffusion effect between multiple main components, the high-entropy alloy nanoparticles are stably anchored and their electronic structure is regulated in the carbon support. Furthermore, 1H-1,2,3-triazole is used as a ligand to achieve high nitrogen doping during pyrolysis, solving the low ORR problem of FeCoNiMoW high-entropy alloy composites while retaining their excellent OER performance.
[0017] Furthermore, the zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt are at least one of the chloride, acetylacetone, and nitrate salts of the corresponding metals. By explicitly listing a variety of commercially available and low-cost common metal salts as raw materials, the range of raw material sources is greatly expanded, enhancing the universality and flexibility of the preparation method. This allows those skilled in the art to flexibly select raw materials based on availability, cost, or specific reaction requirements, which helps reduce production costs and facilitates the large-scale industrial application of this method.
[0018] Furthermore, the nitrogen-containing organic ligand is 1H-1,2,3-triazole, a high-nitrogen-content small organic molecule that serves as a ligand to construct a metal-organic framework precursor in the solvothermal reaction and as a nitrogen source in the subsequent high-temperature heat treatment. This ensures efficient in-situ nitrogen doping in the final product, forming abundant MN (metal-nitrogen) active sites. These sites not only significantly enhance the intrinsic activity of the catalyst but also anchor it firmly to the carbon matrix through strong interactions with high-entropy alloy nanoparticles, thereby greatly improving the structural stability and durability of the catalyst.
[0019] Furthermore, the ratio of ethanol, deionized water, N,N-dimethylformamide, and ammonia is 2:3:2:1. This specific ratio of mixed solvent provides an optimal solvent environment for the complete dissolution of the metal salt and the uniform reaction with the organic ligand. The synergistic effect of different solvents (such as the strong solubility of DMF and the pH-regulating effect of ammonia) can precisely control the kinetics and thermodynamic processes of the solvothermal reaction, thereby ensuring the formation of a metal-organic framework precursor with uniform morphology and component distribution. This is a key prerequisite for obtaining a high-performance final catalyst.
[0020] Furthermore, the solvothermal reaction is conducted at a temperature of 120–160 °C for a duration of 12–36 h. This optimized reaction condition range ensures a sufficient and complete coordination reaction between the metal ions and the organic ligands, resulting in a highly crystalline and structurally stable metal-organic framework precursor. Too low a temperature or time will lead to incomplete reaction, while too high a temperature or too long a time will cause precursor decomposition or aggregation. Therefore, this range is a key parameter for balancing the reaction rate, product crystallinity, and structural integrity, laying a solid material foundation for subsequent heat treatment steps.
[0021] Furthermore, the nitrogen-containing organic ligand is added at a rate of 2.5 mL / (5-10) min. This slow addition method effectively controls the nucleation and growth rate of the precursor. If the ligand is added too quickly, it can lead to excessively high local concentrations, triggering explosive nucleation and resulting in uneven precursor particle size and easy aggregation. Slow addition, on the other hand, maintains the reaction system at a low degree of supersaturation, which is beneficial for forming a precursor with uniform size and good dispersion, thereby ensuring the uniformity of the final catalyst structure and the stability of its performance.
[0022] Furthermore, the molar ratio of zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt is 20:1:1:1:1:1. This specific high zinc ratio design is the core of achieving the dual functions of in-situ pore formation and high-entropy alloy formation. The high zinc content acts as a sacrificial agent, volatilizing at high temperatures to generate a large number of atomic-level vacancies. These vacancies aggregate and migrate to form an ideal hierarchical pore structure. The equimolar ratio of the other five metals conforms to the multi-principal-element design concept of high-entropy alloys, which is conducive to the formation of stable high-entropy alloy nanoparticles at high temperatures, leveraging their unique electronic synergistic effect, thereby simultaneously optimizing the pore structure and active sites of the catalyst.
[0023] Furthermore, the high-temperature heat treatment is conducted at 800–1000°C for 1–3 hours. This high-temperature range is essential for triggering a series of key physicochemical transformations. At this temperature, the zinc element in the precursor can fully volatilize to form a hierarchical porous structure. Simultaneously, the remaining five metal atoms gain sufficient energy for long-range diffusion and alloying, forming high-entropy alloy nanoparticles. In addition, the organic ligands also carbonize during this process, forming a nitrogen-doped carbon matrix with a high degree of graphitization. Therefore, this temperature and time range is a critical process window to ensure the successful acquisition of a hierarchical porous, high-entropy alloy, and highly nitrogen-doped carbon three-phase composite structure in the final catalyst. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 Power density histograms for high-entropy alloy electrocatalysts with hierarchical pore structures prepared in Examples 1, 2, and 3 of this invention; Figure 2 The LSV curves of the high-entropy alloy electrocatalysts with hierarchical pore structures prepared in Examples 1, 2 and 3 of this invention in 1M KOH are shown. Figure 3 The CV curves of the high-entropy alloy electrocatalysts with hierarchical pore structures prepared in Examples 1, 2 and 3 of this invention in 0.1 MKOH are shown. Figure 4 Scanning electron microscope image of the high-entropy alloy electrocatalyst with hierarchical pore structure prepared in Example 2 of this invention. Detailed Implementation
[0026] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0027] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0028] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0029] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0030] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0031] This invention provides a method for simultaneously constructing multiple hierarchical pore structures in situ by utilizing the volatilization of high-content Zn and the synthesis of high-entropy alloys, thereby increasing multiple active sites such as strong interfacial MN coordination bonds and effectively improving the electrochemical surface area. This provides an efficient and feasible design scheme for zinc-air battery electrocatalysts.
[0032] Specifically, this invention provides a method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure, comprising the following steps: S1: Dissolve zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt and nickel salt in a mixed solvent, and then add nitrogen-containing organic ligands while stirring to carry out a solvothermal reaction to obtain metal-organic framework precursors; The zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt are at least one of the chloride, acetylacetone salt, and nitrate salts of the corresponding metals; The nitrogen-containing organic ligand is 1H-1,2,3-triazole.
[0033] The mixed solvent is a mixture of ethanol, deionized water, N,N-dimethylformamide and ammonia; the ratio of ethanol, deionized water, N,N-dimethylformamide and ammonia is 2:3:2:1.
[0034] The solvothermal reaction is carried out at a temperature of 120℃ to 160℃ for a time of 12 to 36 h. Preferably, the reaction is carried out at 140℃ for 24 h.
[0035] The addition rate of the nitrogen-containing organic ligand is 2.5 mL / (5-10) min; The molar ratio of the zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt is 20:1:1:1:1:1.
[0036] S2: The metal-organic framework precursor is subjected to high-temperature heat treatment under a protective atmosphere, so that some metal elements volatilize to form a hierarchical pore structure in situ, while the remaining metal elements are alloyed to form high-entropy alloy nanoparticles, and finally nitrogen-doped high-entropy alloy electrocatalyst is obtained.
[0037] The protective atmosphere is a mixture of argon and hydrogen.
[0038] The high-temperature heat treatment is performed at a temperature of 800~1000℃ for a holding time of 1~3 hours. Preferably, the reaction is carried out at 900℃ for 2 hours.
[0039] More specifically, the above preparation process is as follows: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl6), and 0.108 g of ferric chloride (FeCl6) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution was denoted as solution A.
[0040] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over a period of about 5 to 10 minutes.
[0041] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, place it in a muffle furnace, heat it at 140°C for 24 hours, and allow it to cool naturally to room temperature after the reaction is complete.
[0042] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form), namely metal-organic framework precursor; e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was then increased from room temperature to 900℃ at a rate of 5℃ / min. This temperature was maintained at 900℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-900℃ high-entropy alloy carbon nanocomposite material.
[0043] This invention utilizes the aggregation and migration of numerous atomic-level vacancies generated by Zn volatilization to achieve in-situ construction of a hierarchical porous structure (micropores-mesopores-macropores). The resulting honeycomb-like structure provides a support for multiple active sites, increasing the electrochemical reaction area. This ultimately yields an excellent zinc-air battery electrocatalyst. The formation of high-entropy alloy nanoparticles containing five metal elements (Fe, Co, Ni, Mo, and W) and the high nitrogen content of the triazole ligand ensures abundant in-situ nitrogen doping of the derived carbon matrix, forming strong interfacial MN coordination bonds and electronic synergistic effects between the nitrogen-doped porous carbon and HEA nanoparticles, increasing active sites and improving catalytic efficiency. This invention uses zinc-enriched triazole-based multimetallic MOFs (HEA-MET-Zn). x Using a single precursor containing six metals (Zn, Fe, Co, Ni, W, and Mo), the high-content Zn volatilization process in a single pyrolysis operation simultaneously enables the in-situ construction of multiple hierarchical porous structures and the formation of high-entropy alloy nanoparticles. The remaining multi-metal atoms undergo thermodynamically driven diffusion and alloy rearrangement at high temperatures. The high nitrogen content of the triazole ligand ensures abundant in-situ nitrogen doping of the derived carbon matrix, forming strong interfacial MN coordination bonds and electronic synergistic effects between the nitrogen-doped porous carbon and the HEA nanoparticles.
[0044] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0045] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0046] Example 1 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl6), and 0.108 g of ferric chloride (FeCl6) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0047] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over a period of about 5-10 minutes.
[0048] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 140°C for 24 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0049] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0050] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was then increased from room temperature to 800℃ at a rate of 5℃ / min. This temperature was maintained at 800℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-800℃ high-entropy alloy carbon nanocomposite material.
[0051] Example 2 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl2), and 0.108 g of ferric chloride (FeCl3) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0052] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over a period of about 5-10 minutes.
[0053] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 140°C for 24 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0054] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0055] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was then increased from room temperature to 900℃ at a rate of 5℃ / min. This temperature was maintained at 900℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-900℃ high-entropy alloy carbon nanocomposite material.
[0056] Example 3 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl2), and 0.108 g of ferric chloride (FeCl3) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0057] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over a period of about 5-10 minutes.
[0058] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 140°C for 24 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0059] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0060] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was then increased from room temperature to 1000℃ at a rate of 5℃ / min. This temperature was maintained at 1000℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-1000℃ high-entropy alloy carbon nanocomposite material.
[0061] Example 4 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl2), and 0.108 g of ferric chloride (FeCl3) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0062] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over approximately 5 minutes.
[0063] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 120°C for 36 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0064] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0065] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was increased from room temperature to 900℃ at a rate of 5℃ / min. It was held at 900℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-1000℃ high-entropy alloy carbon nanocomposite material.
[0066] Example 5 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl2), and 0.108 g of ferric chloride (FeCl3) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0067] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over approximately 5 minutes.
[0068] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 160°C for 12 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0069] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0070] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was increased from room temperature to 900℃ at a rate of 5℃ / min. It was held at 900℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-1000℃ high-entropy alloy carbon nanocomposite material.
[0071] Example 6 A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure includes the following steps: a. Weigh out 1.09 g of anhydrous zinc chloride (ZnCl2), 0.08 g of molybdenum chloride (MoCl5), 0.07 g of tungsten chloride (WCl6), 0.0952 g of cobalt chloride (CoCl2), and 0.108 g of ferric chloride (FeCl3) using an electronic balance. 0.0951 g of nickel chloride (NiCl2·6H2O) was dissolved in a mixed solvent of 15 mL ethanol + 22.5 mL deionized water + 15 mL DMF + 7.5 mL ammonia. The mixture was ultrasonically dispersed for 30 minutes to ensure complete dissolution of the salts. This solution is denoted as A.
[0072] b. Under magnetic stirring, slowly add 2.5 mL of 1H-1,2,3-triazole to solution A over approximately 5 minutes.
[0073] c. Transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene, seal it, and place it in a muffle furnace. Heat at 140°C for 24 hours. After the reaction is complete, allow it to cool naturally to room temperature.
[0074] d. Filter and collect the solid product, wash three times with DMF, and then three times with ethanol to remove impurities. Dry the solid in a vacuum oven at 140°C for 16 hours, and grind it to obtain HEA-MET-Zn. 0.8 Precursor (powder form).
[0075] e. Approximately 100 mg of HEA-MET-Zn 0.8 The precursor was uniformly spread in an alumina crucible, and argon / hydrogen gas was introduced (flow rate 50-100 mL / min) for 30 minutes to purge air. The temperature was increased from room temperature to 900℃ at a rate of 5℃ / min. It was held at 900℃ for 2 hours to allow zinc to volatilize and form a high-entropy alloy. The temperature was then reduced to room temperature at a rate of 5℃ / min. Heating was then turned off, and the furnace was allowed to cool naturally to room temperature (avoiding quenching to promote alloy formation). The resulting black powder is the FeCoNiMoW@NC-1000℃ high-entropy alloy carbon nanocomposite material.
[0076] Figure 1 The bar charts show the power density of the high-entropy alloy electrocatalysts with hierarchical pore structures prepared in Examples 1, 2, and 3 of this invention. As can be seen from the figures, the prepared materials exhibit high electrical conductivity, with Example 2 showing the highest conductivity, reaching 220 mW / cm². -2 .
[0077] Figure 2 The figures show the LSV curves of the high-entropy alloy electrocatalysts with hierarchical pore structures prepared in Examples 1, 2 and 3 of this invention in 1M KOH. As can be seen from the figures, the LSV curves show excellent oxygen evolution reaction, which is much higher than that of common electrocatalysts, and can meet the general application scenarios of solid-state zinc-air batteries.
[0078] Figure 3 The figure shows the CV curves of the high-entropy alloy electrocatalysts with hierarchical pore structure prepared in Examples 1, 2 and 3 of this invention in 0.1 MkOH. As can be seen from the figure, the CV curves show that they have good oxygen reduction reaction and can meet the general application scenarios of solid-state zinc-air batteries.
[0079] Figure 4 The scanning electron microscope image shows the high-entropy alloy electrocatalyst with hierarchical pore structure prepared in Example 2 of this invention. As can be seen from the figure, the prepared material has a variety of hierarchical pore structures, which is beneficial to the transport of ions in the solid electrolyte. This also explains why the high-entropy alloy electrocatalyst has excellent power density.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure, characterized in that, Includes the following steps: S1: Dissolve zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt in a mixed solvent, and then add nitrogen-containing organic ligands while stirring to carry out a solvothermal reaction to obtain a metal-organic framework precursor; the mixed solvent is a mixture of ethanol, deionized water, N,N-dimethylformamide, and ammonia. S2: The metal-organic framework precursor is subjected to high-temperature heat treatment under a protective atmosphere, so that some metal elements volatilize to form a hierarchical pore structure in situ, while the remaining metal elements are alloyed to form high-entropy alloy nanoparticles, and finally nitrogen-doped high-entropy alloy electrocatalyst is obtained.
2. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt are at least one of the chloride, acetylacetone salt, and nitrate salts of the corresponding metals.
3. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The nitrogen-containing organic ligand is 1H-1,2,3-triazole.
4. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The ratio of ethanol, deionized water, N,N-dimethylformamide and ammonia is 2:3:2:
1.
5. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The solvothermal reaction is carried out at a temperature of 120~160℃ for a time of 12~36 h.
6. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The nitrogen-containing organic ligand was added at a rate of 2.5 mL / (5-10) min.
7. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The molar ratio of the zinc salt, molybdenum salt, tungsten salt, cobalt salt, iron salt, and nickel salt is 20:1:1:1:1:
1.
8. The method for preparing a nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical porous structure according to claim 1, characterized in that, The high-temperature heat treatment is performed at a temperature of 800~1000℃ for 1~3 hours.
9. A nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure, characterized in that, It is prepared by the method described in any one of claims 1 to 8.
10. The application of the nitrogen-doped high-entropy alloy electrocatalyst with a hierarchical pore structure as described in claim 9 in a zinc-air battery.